Prone versus Supine Position during Surgery for Supracondylar Humeral Fractures. (August 2016) - Guler, Olcay; Mutlu, Serhat; Isyar, Mehmet; Mutlu, Harun; Cerci, Halis; Mahirogullari, Mahir
Purpose: To compare the supine versus prone position in closed reduction and percutaneous pinning for supracondylar humeral fractures in children in terms of patient characteristics and outcome. Methods: Records of 25 girls and 31 boys aged 4 to 9 (mean, 6.7) years who underwent closed reduction and percutaneous pinning in the prone (n=27) or supine (n=29) position each by one experienced surgeon for supracondylar extension type-3 humeral fractures were reviewed. Results: The prone and supine groups were comparable in terms of patient characteristics and outcome, except that anaesthesia duration was shorter in surgery performed in the supine position (46.7 vs. 37.2 minutes, p<0.001). Conclusion: In surgery for supracondylar humeral fractures in children, patient position affected only the duration of anaesthesia.